Gradually weaning goat kids may improve weight gains while reducing weaning stress and increasing creep feed intakes - Vickery, Holly M.; Neal, Rachael A.; Stergiadis, Sokratis; Meagher, Rebecca K. (Frontiers in Veterinary Science, 2023)
Most dairy goat farms rear kids on ad libitum milk replacer, calf research suggests this improves growth and welfare, but solid feed intakes are problematic. Weaning can be gradual (incremental milk reduction) or abrupt (sudden, complete milk removal, which evidence suggests reduces welfare). Three treatments were created; abrupt weaning (AW: ad libitum milk until weaning), gradual weaning (milk ad libitum until d35, then milk unavailable 3.5h/d until d45 when milk removal was a 7h/d block (gradual weaning 1: GW1), or 2 x 3.5h/d blocks (gradual weaning 2; GW2)); complete milk removal occurred at d56 for all. Experiment 1 investigated on-farm feasibility, behaviour and Average Daily Gain (ADG). Experiment 2 investigated feed intakes, behaviour and ADG for AW and GW2. Experiment 1 had 261 kids (nine pens of 25-32), CCTV recorded 6h/d and group-level scan sampling recorded target behaviours. Kruskal-Wallis tests showed GW2 kids spent more time feeding on solids during weaning (p = 0.001) and displayed lower levels of ‘frustrated suckling motivation’ PostWean (p = 0.008). However, feeding competition differed PreWeaning (p = 0.007). ADG data from 159 female kids analysed by a General Linear Model (fixed factor: treatment; covariate: 34d weight) found GW2 had highest ADG from 35-45d (p = <0.001), no differences from 45-56d and AW had highest ADG PostWean (56-60d). Experiment 2 had two AW pens (9 kids/pen) and two GW2 pens (8 and 9 kids/pen). A computerised feeder recorded milk intakes from 22-56d. Pen-level solid feed/water intakes were recorded from 14-70d. General Linear Models (fixed factor: treatment; covariate: PreWean value) found GW2 kids had higher ADG (p = 0.046) and lower milk intake (p = 0.032) from 45-55d, and PostWean (56-70d) trended towards GW2 higher ADG (p = 0.074). Mann-Whitney U tests showed pen-level feed intake differences: AW had higher creep and straw throughout, GW2 showed higher creep during weaning (35-55d), and higher water PostWean (>56 d). Behavioural observations suggest that gradually weaned kids may have enhanced welfare. Pen-level gradual weaning is feasible, and whilst weight gain results were mixed, it reduces milk intake, increases creep intake, and therefore combined with behavioural evidence can be recommended.